MENGGUNAKAN MEDIA BONEKA TANGAN UNTUK MENINGKATAN KETERAMPILAN DALAM BERDONGENG SISWA KELAS IX-5 SMP NEGERI 4 TEBING TINGGI - Gloria Samosir (PGSD Universitas Negeri Medan, 2018)
This study aims to improve the storytelling skills of students of Class IX-5 of SMP Negeri 4 Tebing Tinggi using hand puppet media. This research is a classroom action research conducted at SMP Negeri 4 Tebing Tinggi. The research subjects were Class IX-5 students consisting of 36 students. This study consisted of two cycles. Each cycle consists of four stages, namely planning, carrying out actions, observations, reflections. The research instruments in the form of field notes, observation sheets, questionnaires, and assessment sheets told stories. Product upgrading can be seen from the increase in the score of students' storytelling results in each cycle. The average ability of students to tell stories before the action is categorized as lacking. However, after the implementation of the action for two cycles, the average ability of students in storytelling became a good category. Improved product quality / results can be seen from the comparison of the average score of storytelling students in the pre-action stage until after the Cycle II action. The average score of students in the pre-action stage was 19.17, in Cycle I it increased to 23.03, and in Cycle II it increased again to 25.89. Keywords: Hand Puppet Media, Storytelling SkillsThis study aims to improve the storytelling skills of students of Class IX-5 of SMP Negeri 4 Tebing Tinggi using hand puppet media. This research is a classroom action research conducted at SMP Negeri 4 Tebing Tinggi. The research subjects were Class IX-5 students consisting of 36 students. This study consisted of two cycles. Each cycle consists of four stages, namely planning, carrying out actions, observations, reflections. The research instruments in the form of field notes, observation sheets, questionnaires, and assessment sheets told stories. Product upgrading can be seen from the increase in the score of students' storytelling results in each cycle. The average ability of students to tell stories before the action is categorized as lacking. However, after the implementation of the action for two cycles, the average ability of students in storytelling became a good category. Improved product quality / results can be seen from the comparison of the average score of storytelling students in the pre-action stage until after the Cycle II action. The average score of students in the pre-action stage was 19.17, in Cycle I it increased to 23.03, and in Cycle II it increased again to 25.89. Keywords: Hand Puppet Media, Storytelling Skills